Synchrotron based X-ray radiography of convergent shock waves driven by underwater electrical explosion of a cylindrical wire array - Yanuka,D; Theocharous,S; Efimov,S; Bland,SN; Rososhek,A; Krasik,YE; Olbinado,MP; Rack,A (Journal of Applied Physics, 2019)
We present X-ray radiography images showing the propagation of shock waves generated by electrical explosion of a cylindrical arrangement of wires in water driven by pulsed power. In previous experiments [S. N. Bland et al., Phys. Plasmas 24, 082702 (2017)], the merger of shock waves from adjacent wires has produced a highly symmetrical, cylindrical shock wave converging on the axis, where it is expected to produce a high density, strongly coupled plasma ideal for warm dense matter research. However, diagnostic limitations have meant that much of the dynamics of the system has been inferred from the position of the front of the cylindrical shock and timing/spectra of light emitted from the axis. Here, we present a synchrotron-based radiography of such experiments—providing direct quantitative measurements on the formation of the convergent shock wave, the increased density of water on the axis caused by its arrival, and its “bounce” after arrival on the axis. The obtained images are compared with two-dimensional hydrodynamic simulations, which reproduce the observed dynamics with a satisfactory agreement in density values.